Race and Policy - House, Ernest R. (Education Policy Analysis Archives, 1999)
Beliefs about race have played a central role in American history, literature, and education. Racial beliefs are embedded in the national identity in complex and disguised ways. These beliefs attribute presumed character traits to African Americans and other minorities, who are thought of as different in character and ability, especially the ability to govern themselves. These beliefs lead to education policies which separate, differentiate, and mandate different curricula and treatment for minorities, policies justified as being fair and democratic. These beliefs influence not only curriculum content, but how the schools are organized, financed, and administered at a deeper level than is commonly understood.